2002
DOI: 10.1046/j.1525-1594.2002.07005_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Right Ventricular Outflow Tract with Stentless Xenografts in Ross Procedure

Abstract: To investigate whether the use of a stentless porcine aortic xenograft can be an alternative for right ventricular outflow tract (RVOT) reconstruction during the Ross procedure, 9 patients underwent the Ross procedure and RVOT reconstruction with a stentless xenograft since January 2000. After the aortic valve was replaced with a pulmonary autograft, a stentless xenograft with a xeno- pericardial roll was implanted in the RVOT. One patient required subsequent aortic valve replacement because of severe regurgit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…12 Although excellent results using stentless valves for RVOT reconstruction were reported, there have been some reports about increasing PGs in the pulmonary position after RVOT reconstruction. 4,8,13 In our study, ePTFE-valved conduits for RVOT reconstruction did not increase the PG in the pulmonary position. Because the possibility of calcifi cation is reduced when using ePTFE materials, we can expect good long-term results with ePTFE valved conduits.…”
Section: Discussionsupporting
confidence: 41%
“…12 Although excellent results using stentless valves for RVOT reconstruction were reported, there have been some reports about increasing PGs in the pulmonary position after RVOT reconstruction. 4,8,13 In our study, ePTFE-valved conduits for RVOT reconstruction did not increase the PG in the pulmonary position. Because the possibility of calcifi cation is reduced when using ePTFE materials, we can expect good long-term results with ePTFE valved conduits.…”
Section: Discussionsupporting
confidence: 41%
“…It appears that valve gradients increase during follow‐up. All six studies addressed this issue, five found an increase in valve gradients from discharge to end of follow‐up and one 12 found no significant difference. The difference in means between valve gradient (in mm Hg) at discharge and follow‐up in each study is reported in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, this study investigated a pediatric population; an early active inflammatory reaction resulting in extrinsic compression and shrinkage can, therefore, not be ruled out. No increase in valve gradients were seen in the cohort by Tsukube et al 12 Only three studies directly compared the Freestyle SX. Miskovic et al 10 and Weimar et al 13 highlighted the issue of higher rate of reintervention and pulmonary valve dysfunction when using Freestyle SX in the pulmonic position, suggesting that the higher peak gradients may have clinical impact.…”
Section: Summary Of Evidencementioning
confidence: 93%
See 1 more Smart Citation
“…This resulted in good hemodynamic results at midterm, without concomitant tissue proliferation. 33 In this context, the rational for implantation of the novel designed valved conduit as pulmonary valve substitute in GUCH patients was the avoidance of direct contact of the stentless xenograft with the RVOT muscle component by an already described surrounding vascular prosthesis. The current literature has pointed out significantly higher pressure gradients across the stentless xenografts in GUCH patients at 1-year follow-up compared with homografts.…”
Section: Discussionmentioning
confidence: 99%